Improvement of Operational Flexibility for Active Distribution Networks Based on Soft Open Points - Quan XU; Zhiyong YUAN; Jinyong LEI; Yuehuan LIN; Hao BAI; Peng LI (Zhongguo dianli)
With the high penetration of distributed generators (DGs), it is more complicated for the operational scenarios and puts a higher requirement for the operational flexibility in active distribution networks (ADNs). The operational flexibility of ADNs is based on the controllable resources in it. The increasing integration of flexible resources such as soft open point (SOP) provides opportunities for further improvement of operational flexibility in distribution networks. In this paper, to quantify the improvement of flexibility by SOP, a quantification method of operational flexibility in ADNs is proposed. The definition of operational flexibility is proposed firstly. By constructing a multi-dimensional state space, state equations of operational constraints and an analytical framework for quantifying improvement of operational flexibility are proposed. Then the mathematical expressions of SOP are proposed and the mechanism of improving operational flexibility is discussed. Finally, based on the Monte-Carlo simulation, case studies are performed on the modified IEEE 33-node system to quantify the improvement of operational flexibility by integration of SOP.